The THE IN DUBIO PRO SOCIETATE IN THE BRAZILIAN LEGAL SYSTEM UNDER THE PERSPECTIVE OF ALEXY’S THEORY OF PRINCIPLES (Reflection and Critique Law Magazine, 2023)
This article analyze the possibility of applying the phrase in dubio pro societate at the time of the pronunciation decision in cases where there is no certainty regarding the authorship of the crime, given the absence of legal provision in this regard, in contrast to the presumption of innocence constitutionally guaranteed. This will happen through the analysis of the normativity of this supposed principle in the national legal order, taking into account the modern distinction between principles and rules proposed by Alexy. In addition, it presents the confrontation of in dubio pro societate, which does not find support in the criminal legislation and criminal procedure of the country with current legal and constitutional principles, such as presumption of innocence and in dubio pro reo.